2012
DOI: 10.1007/s11033-012-1677-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polysaccharides extract of rhizoma atractylodis macrocephalae on thymus, spleen and cardiac indexes, caspase-3 activity ratio, Smac/DIABLO and HtrA2/Omi protein and mRNA expression levels in aged rats

Abstract: This study was designed to determine the possible protective effect of polysaccharides extract of rhizoma atractylodis macrocephalae on heart function in aged rats. Polysaccharides extract of rhizoma atractylodis macrocephalae was administered to aged rats. Results showed that thymus, spleen and cardiac indexs were significantly increased, whereas caspase-3 activity ratio, Smac/DIABLO and HtrA2/Omi protein expression, Smac/DIABLO and HtrA2/Omi mRNA expression levels were markedly reduced. It can be concluded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Our and other’s previous studies showed the expression of Omi/HtrA2 is increased in the aging heart, which promotes cardiomyocyte apoptosis via degradation of XIAP and plays a causative role in enhanced post-ischemic injury in the aging heart1017. Here, we confirmed these findings using a transgenic model of mitochondrial Omi/HtrA2 overexpression that mimicked the conditions of an aged heart.…”
Section: Discussionsupporting
confidence: 86%
“…Our and other’s previous studies showed the expression of Omi/HtrA2 is increased in the aging heart, which promotes cardiomyocyte apoptosis via degradation of XIAP and plays a causative role in enhanced post-ischemic injury in the aging heart1017. Here, we confirmed these findings using a transgenic model of mitochondrial Omi/HtrA2 overexpression that mimicked the conditions of an aged heart.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study has reported that the polysaccharides extract of Atractylodes macrocephala enhanced immunity and improved heart function in aged rats (Guo et al, 2012). However, little is known regarding the role of Atractylodes macrocephalaon polysaccharides (AMP) in macrophage activation.…”
Section: Introductionmentioning
confidence: 99%
“…Cortex Cinnamomi has been found to improve renal function effectively in mice 36. Furthermore, the bioactive components or extracts of the Atractylodis macrocephalae rhizome have been reported to enhance immunity in aged rats 37. In summary, these reports indicate that Wuling San might have diuretic efficacy and renal protective effects by enhancing kidney function and inhibiting stress response.…”
Section: Discussionmentioning
confidence: 93%